PENGEMBANGAN KOGNITIF PADA ANAK USIA DINI MELALUI MEDIA BERMAIN - Muh Imron Rosyadi (LP2M STIT Al-Hikmah Way Kanan, 2020)
Abstract This study aims to determine the process and learning outcomes as an effort to improve children's cognitive development through fishing play media for group B children in Miftahul Huda Kindergarten, East OKU Regency. This type of research is Classroom Action Research (CAR). This study uses Kemmis and Mc Taggart designs. Each cycle consists of four stages: planning, implementing actions, observing, and reflecting. The subjects of the study were children of group B kindergarten Miftahul Huda. Data collection techniques are done through observation, interviews and documentation studies. The collected data were analyzed descriptively qualitatively and quantitatively. The results showed the cognitive development of children before the action was still in the category began to develop namely 58.55%; the results of the first cycle research reached 69.62% in the developing category and the second cycle reached 80.99% in the highly developed category; the use of playing fishing media has a very good effect shown by the cognitive development of children who experience very good development compared to before the action Keywords: Cognitive, Play Media